Processo de tomada de decisão baseado em evidências e experiência prática em uma empresa de saúde de médio porte - Kuhn, Alisson Augusto Carnelos (2022)
This work is in the context of a company in the health sector. Currently, decision-making related to Software Engineering (SE) is challenging, as there is no process to guide the activities involved in decision-making, and professionals make their choices with restricted information, usually considering practical experiences. The use of Evidence-Based Software Engineering (ESBE) techniques, such as Quick Reviews associated with Gray Literature, makes it possible to identify theoretical evidence to associate it with practical experience to help the choice process in decisions related to ES. Objective: Our goal was to define a decision-making process associating different sources of information, such as theoretical and practical sources. Method: We followed the five steps of the Research-Action method: (1) Diagnosis - Initially, we diagnosed the company's decision-making process to identify the variables involved in the current process; (2) Planning - Next, decision processes existing in the literature were analyzed; (3) Taking action - Based on the diagnosis and the findings of the literature, a process was proposed, considering the use of scientific evidence- quantitative data; and also practical experiences - qualitative data. Synthesis methods to aggregate qualitative and quantitative data, such as the Bayesian synthesis, were adopted; (4) Evaluation - We evaluated the proposed decision-making process through a case study; and (5) Reflection - Finally, we analyzed the findings both from the perspective of the company and the research.